A novel sleep stage scoring system: Combining expert‐based features with the generalized linear model. (7th February 2020) - Gunnarsdottir, Kristin M.; Gamaldo, Charlene; Salas, Rachel Marie; Ewen, Joshua B.; Allen, Richard P.; Hu, Katherine; Sarma, Sridevi V.
Abstract: In this study, we aim to automate the sleep stage scoring process of overnight polysomnography (PSG) data while adhering to expert‐based rules. We developed a sleep stage scoring algorithm utilizing the generalized linear modelling (GLM) framework and extracted features from electroencephalogram (EEG), electromyography (EMG) and electrooculogram (EOG) signals based on predefined rules of the American Academy of Sleep Medicine (AASM) Manual for Scoring Sleep. Specifically, features were computed in 30‐s epochs in the time and frequency domains of the signals and were then used to model the probability of an epoch being in each of five sleep stages: N3, N2, N1, REM or Wake. Finally, each epoch was assigned to a sleep stage based on model predictions. The algorithm was trained and tested on PSG data from 38 healthy individuals with no reported sleep disturbances. The overall scoring accuracy reached on the test set was 81.50 ± 1.14% (Cohen's kappa, κ = 0.73 ± 0.02 ). The test set results were highly comparable to the training set, indicating robustness of the algorithm. Furthermore, our algorithm was compared to three well‐known commercialized sleep‐staging tools and achieved higher accuracies than all of them. Our results suggest that automatic classification is highly consistent with visual scoring. We conclude that our algorithm can reproduce the judgement of a scoring expert and is also highly interpretable. This tool can assist visual scorers to speed up their process (from hours to minutes) and provides a method for a more robust, quantitative, reproducible and cost‐effective PSG evaluation, supporting assessment of sleep and sleep disorders.